Experimental substantiation of the use of highly mineralized bromine chloride sodium water to correct the functional-metabolic continuum in rats with a model of distress - Nasibullin, Boris; Gushcha, Sergey; Dekhtyar, Yuri; Volyanska, Veronika; Plakida, Alexander (Journal of Education, Health and Sport, 2023)
The authors studied the state of the functional-metabolic continuum in white rats while modeling psycho-emotional distress. They evaluated the effect of mineral water with a high content of sodium bromine and chlorides, when applied externally, on the state of the body of the test animals in distress. The model of distress in rats is characterized by rearrangements of metabolic reactions: an increase in endogenous intoxication, an increase in the activity of lipid peroxidation against the background of a decrease in the activity of antioxidant defense enzymes, a reduction in the content of creatinine and urea, a decrease in the energy supply of the activity of transmembrane metabolism and alanine aminotransferase (ALAT) and aspartate aminotransferase (AST). Simultaneously with adverse changes in metabolic reactions, signs of dystrophic changes in internal organs are determined. Course external application of mineral water (MW) with a high content of sodium, chlorides and bromine in rats with psycho-emotional distress significantly improves metabolism. The normalization of energy metabolism and balance in the lipid-antioxidant system of indicators of endogenous intoxication and the restoration of the functional state of the liver confirms this. In the internal organs, manifestations of dystrophy disappear. The authors believe that using MW improves the condition of regulatory processes, thereby restoring the functional-metabolic continuum in distressed rats.